THE RELATIONSHIP BETWEEN ACADEMIC STRESS AND SLEEP QUALITY WITH THE INCIDENCE OF ANEMIA IN ADOLESCENT GIRLS - Titin Novayanti Dey; Sumiati Sumiati (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Anemia among adolescent girls remains an unresolved health problem in Indonesia. Factors suspected to be associated with anemia include academic stress and sleep quality. The study aimed to determine the relationship between academic stress and sleep quality with anemia among 12th-grade female adolescents at Senior High School 1 Rendang, Karangasem Regency. This observational analytical study used quantitative methods and a cross-sectional design with a sample of 92 respondents obtained through total sampling techniques. The measurement tools used included the Educational Stress Scale for Adolescents (ESSA) questionnaire to assess academic stress levels, the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, and hemoglobin levels. Data were analyzed using the Chi-Square test. The results showed that the highest proportion of respondents were in the moderate academic stress category (87.0%), followed by 48.9% with poor sleep quality, and the prevalence of anemia was recorded at 14.1%. Statistically, no relationship was found between academic stress and anemia (p=0.819), nor between sleep quality and anemia (p=0.710).